Contributions to psychological acoustics: results of the Eighth Oldenburg Symposium on Psychological Acoustics - Schick, August; Meis, Markus; Reckhardt, Carsten (Bibliotheks- u. Informationssystem der Univ., 2000)
The essays contained in this volume present the results of a Summer School of the Graduate School 'Psychoacoustics' and the 8th Oldenburg Symposium on Psychological Acoustics. <engl.>
Literaturangaben
Keywords: Konferenzschrift; Oldenburg (Oldenburg); Psychoakustik; Oldenburg <Oldenburg, 1997>